Pemberantasan Kejahatan Ekonomi antar Negara dengan Perjanjian Ekstradisi (Perspektif Indonesia) - Mohd. Burhan Tsani (Jurnal Hukum IUS QUIA IUSTUM, 2000)
The recent case of Edy Tansil and Hendra Rahardja is one of small exarnples of how the development of white colour crime has become trans-national. Thus, Indonesia should be actively involving itself among other countries to provide a settlement of the criminals. Several other countries have an extradition agreement with Indonesia, while others do not. The extradition itself boasts a different view from one country using common lawsystems to one employing civil law systems whether or not the extradition would be allowed, ifthe treaty were not yet proved. This article endeavours the forms ofwhite colour criminals, and what contribution ofthe extradition agreement in precluding the criminals among countries.